2008
DOI: 10.2174/157340708784533393
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Active Natural Products of the Genus Callicarpa

Abstract: About 20 species from Callicarpa have reported ethnobotanical and ethnomedical uses, and several members of this genus are well known in the traditional medical systems of China and South Asia. Ethnomedical reports indicate their use in the treatment of hepatitis, rheumatism, fever, headache, indigestion, and other ailments. Several species of Callicarpa have been reported to be used against cancer (e.g., Callicarpa americana root to treat skin cancer and Callicarpa rubella bark to treat tumors of the large in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…Kamaya et al [4] reported that the growth of S. capricornutum was strongly inhibited by long chain fatty acids. There are still many related reports that can be referenced [5][6][7]. However, from these reports we have found that more studies are focused on controlling freshwater algal blooms, but not red tide, and the mechanism of allelochemicals inhibition on marine microalgae is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Kamaya et al [4] reported that the growth of S. capricornutum was strongly inhibited by long chain fatty acids. There are still many related reports that can be referenced [5][6][7]. However, from these reports we have found that more studies are focused on controlling freshwater algal blooms, but not red tide, and the mechanism of allelochemicals inhibition on marine microalgae is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…There are around 140 species of Callicarpa L. distributed in tropical and subtropical locations [1]. The genus has been placed in either the Verbenaceae or the Lamiaceae, but is currently placed in Lamiaceae [2,3]. Members of the genus have been used as fish poisons and in herbal medicine [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The genus has been placed in either the Verbenaceae or the Lamiaceae, but is currently placed in Lamiaceae [2,3]. Members of the genus have been used as fish poisons and in herbal medicine [1,2]. In this work, we present the essential oil compositions of several Callicarpa species growing wild in central Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…is a perennial mediumsized tree belonging to the family Lamiaceae and is found in China, Nepal, Bhutan, India, Sri Lanka, Bangladesh, and South-East Asian region. In India, Bangladesh and Nepal, the bark is used for the treatment of skin diseases, fever, indigestion, 7 and boils. 8,9 In ayurvedic medicine, it is a medication for rheumatism and paralysis.…”
Section: Introductionmentioning
confidence: 99%